2019
DOI: 10.1016/j.pec.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a primary care training program on the prevention and management of unhealthy alcohol use: A quasi-experimental study

Abstract: Objective: To assess the impact of a training program targeted to Primary Care (PC) professionals on the acquisition of communication skills, attitudes, and knowledge about the prevention and management of unhealthy alcohol use. Methods: A quasi-experimental, pre-and post-intervention study was performed in PC centers of Cordoba (Spain). Family doctors, residents and nurses participated in the study. The intervention was based on a motivational interviewing training program, which consisted in a workshop on le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
5
0
Order By: Relevance
“… 21 This level of knowledge is similar to that obtained in Romero's study. 10 In our study, the level of knowledge improved after the training, the participants passed to answer correctly from 35% to 50% of the questions. However, the above-mentioned study showed a higher increase, with a 22.9% improvement after the intervention.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“… 21 This level of knowledge is similar to that obtained in Romero's study. 10 In our study, the level of knowledge improved after the training, the participants passed to answer correctly from 35% to 50% of the questions. However, the above-mentioned study showed a higher increase, with a 22.9% improvement after the intervention.…”
Section: Discussionmentioning
confidence: 48%
“…Based on a previous study, 10 assuming an alpha risk of 0.05 and a beta risk of 0.2, it would be necessary to include 81 subjects, assuming that the initial proportion of knowledge that was considered “acceptable” (80% of correct questions in both groups) was 35% and after the training intervention, at least 60%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these tools strengthen the patient-healthcare professional relationship and allow, in turn, to improve the patient's perception of the care received, helping us reduce the prevalence of this health problem. Likewise, the present study aims to promote preventive activities and enhance health education on such an important risk factor as alcohol consumption in PC, whose effect has been demonstrated by this research group (29,30), and to provide continuity of care for this important public health problem. Similarly, the research study will help foster knowledge and communication skills and preventive recommendations of PC healthcare professionals, as well as provide support tools to facilitate decisionmaking aimed at reducing alcohol consumption in the general population.…”
Section: Discussionmentioning
confidence: 94%
“…Thanks to the conversations conducted by the nurses and their openness to the problems of the patients, the knowledge acquired during the therapeutic meetings is transferred into the sphere of everyday life experiences. Patients learn how to live with alcoholic illness, make constructive plans, avoid certain situations, and expand the circle of social support [48,49]. According to the results of the study, Tsai and colleagues [50], nurses are aware of the barriers and factors that contribute to effective interventions in alcohol therapy.…”
Section: Discussionmentioning
confidence: 99%